The patterns of fusional area on acquired extraocular muscle disturbances - Kimura, Hisashi; Fukai, Sakuko; Sakai, Naoko; Arai, Noriko (JAPANESE ORTHOPTIC JOURNAL, 1995)
We reported the development of fusional area on acquired extraocular muscle disturbance. The subjects were 10 patients with a fusional area of more than 30°·by orthoptic training. Five patients had acquired superior oblique palsy, which is a functional extraocular muscle disturbance. Five had a blowout fracture, which is a mechanical extraocular muscle disturbance. Evaluation of the fusional area was performed using Bagolini Striated Glasses, and its development was showen with patterns. The fusional area of acquired superior oblique palsy was directed against the action paretic muscle, which did not undergo training. In this case the fusional area developed primarily in the direction of the paretic muscle. The fusional area of blowout fracture developed in variable directions. We made clear that in the case of extraocular muscle disturbance, development of the fusional area achived by orthoptic training was different in its origin. In the case of functional extraocular muscle disturbance, the direction of development of the fusionl area suggested that the paretic muscle became functional as a result of the orthoptic training. In the case of mechanical extraocular muscle disturbance, the direction of development of the fusional area suggested that the limitation of eye movement improved. We concluded that the development of fusional areas by orthoptic training was useful for orthoptic management in extraocular muscle disturbance.